Preoperative Hemoglobin Level, Oxygen Saturation and Postoperative Outcomes in Children With Cyanotic Congenital Heart Disease: A Propensity-Score Matching Analysis - Zhou, Dan; Deng, Li-Jing; Ling, Yun-Fei; Tang, Meng-Lin (Frontiers in Pediatrics, 2022)
Background: The optimal preoperative hemoglobin (Hb) level is difficult to define in children with cyanotic congenital heart disease (CHD) due to hypoxemia-induced secondary erythrocytosis. This retrospective study integrated preoperative Hb and pulse oxygen saturation (SpO2) using the product of Hb×SpO2 to predict postoperative outcomes in children with cyanotic CHD. Patients and methods: Children aged <18 years undergoing cardiac surgery with cyanotic CHD were included. The cutoff value of Hb×SpO2 was the age-adjusted lower limit of normal Hb (aaHb) in healthy children. The main outcomes were in-hospital death and the composite outcome of severe postoperative events. Multivariate logistic regression analysis and propensity score matching analysis were used to adjust for important confounders. Results: The presence of preoperative Hb×SpO2